Migrant modernism : postwar London and the West Indian novel - Brown, J. Dillon, 1971- (University of Virginia Press, 2013)
The author examines the intersection between British literary modernism and the foundational West Indian novels that emerged in London after World War II. By emphasizing the location in which anglophone Caribbean writers such as George Lamming, V.S. Naipaul, and Samuel Selvon produced and published their work, the author reveals a dynamic convergence between modernism and postcolonial literature that has often been ignored. Modernist techniques not only provided a way for these writers to mark their difference from the aggressively English, literalist aesthetic that dominated postwar literature in London but also served as a self-critical medium through which to treat themes of nationalism, cultural inheritance, and identity.